PERLINDUNGAN HUKUM TERHADAP PARA PIHAK DALAM PERJANJIAN FRANCHISE DOORSMEER MOBIL (STUDI PADA DOORSMEER MOBIL PAC) - ADAM SUTANTO (PREMISE LAW JURNAL, 2014)
ABSTRACT Franchise is a business or marketing pattern involving cooperation of both parties. This two parties relationship is built on the basis of the agreement. In franchise, the cooperation agreement between both parties is called franchise agreement which functions as a legal guideline that outlines the responsibilities of franchisor and franchisee.The result of this study showed that legal protection for the parties involved in the franchise agreement of PAC car doorsmeer was not balanced in which the franchisor made a standard agreement that must be agreed by all prospective franchisees. In franchise agreement, a breach of contract (agreement) can be peformed by either the franchisee or franchisor. The breach of contract performed by the franchisor is such as the franchisor does notprovide the franchisee with guidance and training on management while the breach of contract performed by the franchisee is that the franchisee does not pay the fee agreed and does not implement the business system/quality standard as agreed in the agreement. Keywords: Legal Protection, Franchise Agreement, Car Doorsmeer